Розробка автоматизованої мобільної платформи - Костилєв, В. В. (ХНУРЕ, 2021)
Both natural and man-made environments contain many obstacles that are difficult or impossible to overcome using traditional types of movement.To solve this problem, a walking robot has been developed using existing developments, which is able to move over rough terrain with high traffic.
Keywords: автоматизована мобільна платформа